A Multidimensional Analysis: Gaps and Convergence Smart City Implementation in Indonesia - Dinda Syufradian Putra; Iswandi Iswandi; Firmansyah Putra; Dimas Subekti (Jurnal Ilmu Sosial dan Humaniora, 2026)
Indonesia continues to face structural challenges in smart city development, as reflected in the global positioning of its major cities in the IMD Smart City Index. In 2025, Jakarta, Medan, and Makassar were ranked 103, 113, and 114, respectively, placing all three cities in the lower tier of global smart city performance. Longitudinal analysis shows a consistent decrease in ranking positions from 2020 to 2025. Jakarta improved from 81 to 103, Medan from 94 to 113, and Makassar from 90 to 114, yet all cities remain structurally constrained within low tiers of global competitiveness. This study critically examines and developing a comprehensive analytical model to capture structural and technological gaps by a comparative analysis of the IMD index, which evaluates two pillars, Structure and Technology, across five dimensions: Health and Safety, Mobility, Opportunities, Activities, and Governance. Using a comparative case study approach with secondary data analysis the findings reveal a measurable structural technological imbalance. Jakarta demonstrates relatively stronger technological performance in digital public services, smart mobility, and health technologies, but remains weak in structural domains such as environmental quality, housing affordability, and social inclusiveness. Conversely, Medan and Makassar exhibit comparatively stronger socio-environmental foundations but lag significantly in technological adoption, particularly in digital governance and smart mobility. The imbalance between structural readiness and technological capacity indicates that smart city development in Indonesia remains fragmented. These findings underscore the need for integrated development strategies that harmonize technological innovation, sustainable infrastructure, and inclusive public services to enhance the global competitiveness of Indonesian cities.